The C-Terminal Domains SnRK2 Box and ABA Box Have a Role in Sugarcane SnRK2s Auto-Activation and Activity - Righetto, Germanna Lima; Sriranganadane, Dev; Halabelian, Levon; Chiodi, Carla G.; Elkins, Jonathan M.; Massirer, Katlin B.; Gileadi, Opher; Menossi, Marcelo; Couñago, Rafael M. (Frontiers in Plant Science, 2019)
Resistance to drought stress is fundamental to plant survival and development. Abscisic acid (ABA) is one of the major hormones involved in different types of abiotic and biotic stress responses. ABA intracellular signaling has been extensively explored in Arabidopsis thaliana and occurs via a phosphorylation cascade mediated by three related protein kinases, denominated SnRK2s (SNF1-related protein kinases). However, the role of ABA signaling and the biochemistry of SnRK2 in crop plants remains underexplored. Considering the importance of the ABA hormone in abiotic stress tolerance, here we investigated the regulatory mechanism of sugarcane SnRK2s - known as SAPKs (Stress/ABA-activated Protein Kinases). The crystal structure of ScSAPK10 revealed the characteristic SnRK2 family architecture, in which the regulatory SnRK2-box interacts with the kinase domain αC helix. To study sugarcane SnRK2 regulation, we produced a series of mutants for the protein regulatory domains SnRK2-box and ABA-box. Mutations in ScSAPK8 SnRK2-box aimed at perturbing its interaction with the protein kinase domain reduced protein kinase activity in vitro. On the other hand, mutations to ScSAPK ABA-box did not impact protein kinase activity but did alter the protein autophosphorylation pattern. Taken together, our results demonstrate that both SnRK2- and ABA-boxes might play a role in sugarcane SnRK2 function.